New acyclic bis phenylpropanoid and neolignans, from Myristica fragrans Houtt., exhibiting PARP-1 and NF-κB inhibitory effects. (1st July 2016) - Muñoz Acuña, Ulyana; Carcache, Peter J. Blanco; Matthew, Susan; Carcache de Blanco, Esperanza J.
Highlights: Myristica fragrans, a highly consumed spice for its culinary and medicinal properties. The present study discovered a new acyclic with K-Ras activity that can be chemically optimized. This is the first report of neolignans from M. fragrans with PARP-1 and NF-κB inhibitory effects. Abstract: The bioassay-guided fractionation of the aril of Myristica fragrans (mace spice) yielded five phenolic compounds, one new acyclic bis phenylpropanoid (1 ) and four previously known phenolic compounds: compounds (1 ) ( S ) 1-(3, 4, 5-trimethoxyphenyl)-2-(3-methoxy-5-(prop-1-yl) phenyl)-propan-1-ol, (2 ) benzenemethanol; α-[1-[2, 6-dimethoxy-4-(2-propen-1-yl)phenoxy]ethyl]-3, 4-dimethoxy-1-acetate, (3 ) odoratisol A, phenol, 4-[(2 S, 3 S )-2, 3-dihydro-7-methoxy-3-methyl-5-(1 E )-1-propenyl-2-benzofuranyl]-2, 6-dimethoxy, (4 ) 1, 3-benzodioxate-5-methanol, α-[1-[2, 6-dimethoxy-4-(2-propenyl)phenoxy]ethyl]-acetate, (5 ) licarin C; benzofuran, 2, 3-dihydro-7-methoxy-3-methyl-5-(1 E )-1-yl-2-(3, 4, 5-trimethoxyphenyl). An NMR tube Mosher ester reaction was used in an approach to characterize and determine the assignment of the absolute configuration of the new isolated chiral alcohol (1 ). The PARP-1 inhibitory activity was evaluated for compound (1 ) (IC50  = 3.04 μM), compound (2 ) (IC50  = 0.001 μM), compound (4 ) (IC50  = 22.07 μM) and compound (5 ) (IC50  = 3.11 μM). Furthermore, the isolated secondary metabolites were tested for NF-κB and K-Ras inhibitory activities. When tested in the p65 assay, compounds (2 ) and (4 ) displayed potent NF-κB inhibition (IC50  = 1.5 nM and 3.4 nM, respectively).